Moving Beyond Carceral Safety Logics in Aotearoa New Zealand - Gordon, Grace (Manchester Metropolitan University, 2025)
Carceral safety logics, which place institutions within the criminal punishment system as a source of safety, continue to dominate globally. Despite their dominance, during the last 5 years in Aotearoa New Zealand, surveys have reported that more people feel less safe (Ministry of Justice, 2023). This article problematises the reliance on carceral safety logics in Aotearoa and explores alternative approaches that may generate more collective and sustainable safety. This article draws on 16 semi-structured interviews with people who advocate or work in the ‘justice’ system to inform this perspective. Narratives shared within these interviews present a desired relational element of safety that is at odds with carceral safety logics and punitive approaches to safety. The participants, from penal populists to penal abolitionists, ultimately saw safety through community-building, ensuring wellbeing needs are met, and collective care. This article unpacks what these shared ideas could mean for abolitionist conceptions of safety and justice in the community.
Keywords: 440206 Critical approaches to crime; 1602 Criminology; 1801 Law; 4402 Criminology; 4805 Legal systems; carceral safety logics; care-based safety; collective care; community safety; prison abolition